Annotated bird sighting list for Winter 1980-1981 compiled by Ruth Phipps - Phipps, Ruth O.et al (1980)
An annotated list of birds sighted by Ruth Phipps and others in southwest Iowa. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed